GEOGEBRA SEBAGAI SOLUSI UNTUK MENGKONSTRUKSI KONSEP-KONSEP MATEMATIKA DI ERA DIGITAL - Kesumawati, Nila (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
The development of technology, especially information technology change the way of view, how to work and also implementation in the field of learning. Knowledge of teachers who are still minimal to digital technology, it is feared will affect the learning process. Math learning in the digital age requires a tool to facilitate understanding of mathematical concepts. Along with technological advances, the mathematical media is also growing rapidly. One of them is the GeoGebra computer application program. GeoGebra is a computer program for learning mathematics especially geometry and algebra. GeoGebra is a dynamic program that has facilities to demonstrate or visualize concepts as well as a tool for constructing mathematical concepts.